PENGUATAN KELEMBAGAAN KOPERASI MELALUI MODAL PENYERTAAN - Karuniana Dianta A. Sebayang (Fakultas Ekonomi Universitas Negeri Jakarta, 2013)
Abstract Cooperative efforts towards the pillar of the national economy should be supported through strengthening institutional cooperatives. As is known in the cooperative governance still have problems like, weak capital structure, business competition, diminishing cooperative image in the eyes of the community, the level of skills and professionalism of human resources inadequate and lack of education and awareness of government agencies. Strengthening the institutional cooperative effort can be made by supporting the empowerment of cooperatives through the capital. Capital support for cooperative development can be given with equity participation by the goverment, business entities, or public sector. To maximize business through equity capital is expected that cooperative be more innovative to attract the attention of investors. Support from the government is also required to create policies that integrative and socialized and internalized the cooperative movement. Keywords: Institutional, Cooperative, Capital Investments